Visualization of Skoda Instrument Cluster - Matus Danko; Michal Taraba; Juraj Adamec; Peter Drgona (Communications - Scientific letters of the University of Zilina, 2018)
Most signals in modern vehicles which are transmitted from sensors to control units or actuators are transmitted via bus. The most common automotive data bus is Controller Area Network(CAN). Some of transmitted signals are speed of the vehicle, engine speed and coolant temperature which are used for visualization of Skoda Octavia instrumental cluster. For this visualization, CAN BUS communication is filtered and processed, to obtain three message objects to observe required data. For data acquisition from bus is used modular system CompactRio with module for CAN BUS from National Instruments. The whole application is created in visual programming language LabVIEW using FPGA module.